2009
DOI: 10.1007/s00415-009-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal motor excitability in patients with psychogenic paresis

Abstract: We suggest that the paradoxical decrease of motor excitability during motor imagery is the electrophysiological correlate of a disturbed voluntary control in motor conversion disorder. The results further indicate that this abnormality is not restricted to the clinically affected body part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…In line with this, we observed a stronger modulatory influence of dlPFC during the generation of action plans of the affected limb that was positive in sign for the PMd and negative in sign for S1. The stronger inhibitory coupling between dlPFC and S1 during motor imagery of the affected hand could also provide an explanation for the decreased excitability of the primary motor cortex that has previously been observed in CP (Liepert et al, 2009). Activity in S1 can strongly contribute to the excitability of the motor system as measured by motor evoked potentials (Avenanti, Bolognini, Maravita, & Aglioti, 2007).…”
Section: Increased Negative Coupling Between Dlpfc and S1 During Imagmentioning
confidence: 81%
See 1 more Smart Citation
“…In line with this, we observed a stronger modulatory influence of dlPFC during the generation of action plans of the affected limb that was positive in sign for the PMd and negative in sign for S1. The stronger inhibitory coupling between dlPFC and S1 during motor imagery of the affected hand could also provide an explanation for the decreased excitability of the primary motor cortex that has previously been observed in CP (Liepert et al, 2009). Activity in S1 can strongly contribute to the excitability of the motor system as measured by motor evoked potentials (Avenanti, Bolognini, Maravita, & Aglioti, 2007).…”
Section: Increased Negative Coupling Between Dlpfc and S1 During Imagmentioning
confidence: 81%
“…For instance, a recent study that directly probed the excitability of the motor cortex using transcranial magnetic stimulation observed striking excitability changes in the motor system during motor imagery of the affected hand in CP (Liepert, Hassa, Tüscher, & Schmidt, 2009). While motor imagery of the unaffected hand resulted in higher motor excitability, as it is normally observed in the healthy population (Abbruzzese, Trompetto, & Schieppati, 1996), motor imagery of the affected hand led to a paradoxical decrease of motor excitability.…”
Section: Introductionmentioning
confidence: 97%
“…In another experiment, the authors described a specific slowing of motor initiation but not a general slowing involving motor execution [30]. Recent TMS studies with patients suffering from psychogenic upper limb paresis demonstrated that MI of finger movements with the affected limb induced a decrease of motor excitability, suggesting an inhibition of the motor system during that task [31,32]. The present study explored if a similar phenomenon can also be found in psychogenic lower limb paresis and if abnormalities occur to a comparable degree in MI and AO, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Liepert et al 32 showed that in response to motor imagery, patients with unilateral functional paralysis (N=5) or fixed dystonia (N=3) had a decrease in MEP of the affected hand by 37%, compared with rest with an increase in MEP by 63% of the unaffected side These findings were specific to MEPs because motor threshold, short intracortical inhibition, and intracortical facilitation were shown to be unremarkable among individuals with functional paralysis. 33,34 In healthy individuals, motor imagery commonly increases MEPs to a level comparable to that observed during executed movements. In a study by Liepert et al, 34 subjects…”
mentioning
confidence: 99%
“…33,34 In healthy individuals, motor imagery commonly increases MEPs to a level comparable to that observed during executed movements. In a study by Liepert et al, 34 subjects…”
mentioning
confidence: 99%